2017
DOI: 10.1371/journal.pone.0188185
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific evolutionary relationships among peregrine falcons in western North American high latitudes

Abstract: Subspecies relationships within the peregrine falcon (Falco peregrinus) have been long debated because of the polytypic nature of melanin-based plumage characteristics used in subspecies designations and potential differentiation of local subpopulations due to philopatry. In North America, understanding the evolutionary relationships among subspecies may have been further complicated by the introduction of captive bred peregrines originating from non-native stock, as part of recovery efforts associated with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…However, postrecovery samples indicated that tundrius and anatum could be differentiated due to increased genetic diversity within southern anatum populations, likely due to use of exotic subspecies for captive breeding during the recovery phase (Brown 2007). Similarly, using Alaskan samples, Talbot et al (2017) indicated that although pealei could be genetically differentiated from tundrius and anatum, the latter two subspecies could not be distinguished genetically. Using samples collected during migration (1985 to 2007) at Padre Island, Texas, Johnson et al (2010) found little difference between tundrius and anatum, and suggested that delineation between the two subspecies breeding at northern latitudes was not justified.…”
Section: Diversitymentioning
confidence: 98%
“…However, postrecovery samples indicated that tundrius and anatum could be differentiated due to increased genetic diversity within southern anatum populations, likely due to use of exotic subspecies for captive breeding during the recovery phase (Brown 2007). Similarly, using Alaskan samples, Talbot et al (2017) indicated that although pealei could be genetically differentiated from tundrius and anatum, the latter two subspecies could not be distinguished genetically. Using samples collected during migration (1985 to 2007) at Padre Island, Texas, Johnson et al (2010) found little difference between tundrius and anatum, and suggested that delineation between the two subspecies breeding at northern latitudes was not justified.…”
Section: Diversitymentioning
confidence: 98%
“…Secondly, increases in the biases of genetic diversity metrics, influx of new alleles/haplotypes, population growth inferred in Bottleneck (Arctic), and variance of Ne across Pcrit values in post-decline periods suggest the recovery was also augmented by natural immigration. Prior research found that gene flow estimates among regions (post-decline) are asymmetric between Arctic Canada and Arctic Alaska (microsatellite data) and between Interior Alaska and Arctic Alaska (mtDNA data), with no genetic structure detected between Interior and Arctic Alaska (Talbot et al 2017). Thus Peregrine Falcons were probably dispersing across the landscape as populations recovered.…”
Section: Discussionmentioning
confidence: 97%
“…Prior research found that gene flow estimates among regions (post‐decline) are asymmetric between Arctic Canada and Arctic Alaska (microsatellite data) and between Interior Alaska and Arctic Alaska (mtDNA data), with no genetic structure detected between Interior and Arctic Alaska (Talbot et al . 2017). Thus Peregrine Falcons were probably dispersing across the landscape as populations recovered.…”
Section: Discussionmentioning
confidence: 99%
“…Even thought we classified the overwintering individuals into subspecies, it is important to men?on the debate around this subject: many authors argue about the validity of the dis-?nc?on between F. p. anatum and F. p. tundrius based on morphological characters, due the process used for the reintroduc?on of the species in North America (Brown et al 2007, Talbot et al 2017. Analysis of the evolu?onary rela?onship between the three North American subspecies suggests that there is no gene?c differen?a?on from individuals iden?fied as F. p. tundrius and F. p. anatum from higher la?tudes; besides, there is gene flow between popula?ons of these subspecies and a high percentage of shared haplotypes (Talbot et al 2017). Nevertheless, the subspecies does not seem to affect migra?on ?ming and distribu?on in the wintering grounds (Table 1).…”
Section: Discussionmentioning
confidence: 99%